Factors Influencing Mothers’ Interest In Monitoring Infant Development at Fathya General and Maternity Clinic, Medan - Miranda Sari Putri; Listiani Listiani; Mahmudiah Mahmudiah; Manis Nopel P. Tampubolon; Misma Misma; Debora Paninsari (Universitas Malahayati Lampung, 2025)
ABSTRACT Monitoring infant development is essential to ensure optimal achievement both physically and cognitively. In Indonesia, the implementation of infant monitoring still faces various challenges, particularly those related to maternal sociodemographic factors. This study aims to identify the sociodemographic factors that influence mothers’ interest in monitoring infant development at Fathya General and Maternity Clinic in Medan in 2024. The study employs a cross-sectional design involving 30 mothers with infants aged 0–12 months, selected using simple random sampling. Data were collected through a structured questionnaire and analyzed descriptively using SPSS. The results indicate that the majority of respondents belong to the 25–35 years age group (50%), with higher education being the dominant level (43.3%), and 53.3% of the respondents are housewives. The distribution of mothers’ interest in monitoring infant development shows that 50% of respondents stated “Disagree,” 33.3% “Agree,” and 16.7% “Strongly Agree,” with no respondents choosing “Strongly Disagree.” These findings suggest that although most respondents have a high educational background, their interest in monitoring infant development is not optimal. Enhancing educational and socialization programs regarding the importance of infant monitoring is necessary to encourage more proactive participation among mothers. Keywords: Knowledge, Age, Education, Interest, Infant Development ABSTRAK Pemantauan tumbuh kembang bayi sangat penting untuk memastikan pencapaian optimal baik secara fisik maupun kognitif. Di Indonesia, pelaksanaan pemantauan masih menghadapi berbagai tantangan, terutama yang berkaitan dengan faktor sosiodemografi ibu. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor sosiodemografi yang mempengaruhi minat ibu dalam pemantauan tumbuh kembang bayi di Klinik Umum dan Bersalin Fathya Medan pada tahun 2024. Penelitian menggunakan desain cross-sectional dengan melibatkan 30 responden ibu yang memiliki bayi usia 0–12 bulan, dipilih secara simple random sampling. Data dikumpulkan melalui kuesioner terstruktur dan dianalisis secara deskriptif menggunakan SPSS. Hasil penelitian menunjukkan bahwa mayoritas responden berada pada kelompok usia 25–35 tahun (50%), dengan tingkat pendidikan yang dominan adalah Perguruan Tinggi (43,3%), serta 53,3% merupakan ibu rumah tangga. Distribusi minat ibu dalam pemantauan tumbuh kembang bayi memperlihatkan bahwa 50% responden menyatakan “Tidak Setuju”, 33,3% “Setuju”, dan 16,7% “Sangat Setuju”, sedangkan tidak terdapat responden yang memilih “Sangat Tidak Setuju”. Temuan ini mengindikasikan bahwa meskipun sebagian besar responden memiliki latar belakang pendidikan yang tinggi, minat dalam pemantauan tumbuh kembang bayi belum optimal. Peningkatan program edukasi dan sosialisasi mengenai pentingnya pemantauan bayi perlu dilakukan untuk mendorong partisipasi ibu secara lebih proaktif. Kata Kunci: Pengetahuan, Usia, Pendidikan, Minat, Tumbuh Kembang Bayi